2020
DOI: 10.1017/s095457942000084x
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of risk and protective factors associated with internalizing symptoms in autism spectrum disorder: A scoping review, synthesis, and call for more research

Abstract: This paper reviews and synthesizes key areas of research related to the etiology, development, and maintenance of internalizing symptoms in children, adolescents, and adults with autism spectrum disorder (ASD). In developing an integrated conceptual model, we draw from current conceptual models of internalizing symptoms in ASD and extend the model to include factors related to internalizing within other populations (e.g., children that have experienced early life stress, children with other neurodevelopmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 164 publications
(162 reference statements)
1
8
0
4
Order By: Relevance
“…Similarly, while VR was found to improve other types of avoidance (e.g., agoraphobic avoidance, cognitive avoidance, food avoidance, and alcohol-approach avoidance) that are linked to disorders outside of the anxiety category (e.g., psychosis, PTSD, substance-use disorders, and eating disorders, respectively) [ 40 , 43 , 48 , 53 , 57 ], our review of the literature was not able to find more than a few studies for these factors and clinical populations. Indeed, since the literature showed that different kinds of avoidance can be involved in the maintenance or development of different kinds of pathologies [ 81 , 82 , 83 ], investing in a VR software capable of tackling this factor transdiagnostically would be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while VR was found to improve other types of avoidance (e.g., agoraphobic avoidance, cognitive avoidance, food avoidance, and alcohol-approach avoidance) that are linked to disorders outside of the anxiety category (e.g., psychosis, PTSD, substance-use disorders, and eating disorders, respectively) [ 40 , 43 , 48 , 53 , 57 ], our review of the literature was not able to find more than a few studies for these factors and clinical populations. Indeed, since the literature showed that different kinds of avoidance can be involved in the maintenance or development of different kinds of pathologies [ 81 , 82 , 83 ], investing in a VR software capable of tackling this factor transdiagnostically would be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, positive self-perception, positive parenting, and social acceptance were found to provide buffers against the negative effects of ADHD-related symptoms [61••]. To date, studies concerning protective factors in individuals with ASD are scarce [62] and mainly focused on protective factors for the development of internalizing symptoms [63], assuming that less internalizing symptoms would lead to better HRQoL. More specifically, the studies particularly focused on positive parenting and positive peer relationships as protective factors.…”
Section: Future Directions For Research: Protective Factorsmentioning
confidence: 99%
“…More specifically, the studies particularly focused on positive parenting and positive peer relationships as protective factors. The results of the review showed that, in regard to positive parenting studies, results were inconclusive, but positive peer relationships were found to act as a protective factor for internalizing problems [63]. In DCD, the focus of research has mainly been on protective factors that increase resilience to mental health problems, such as high IQ, high self-esteem, good social communication skills, and absence of bullying [64].…”
Section: Future Directions For Research: Protective Factorsmentioning
confidence: 99%
“…Several studies have examined whether co‐occurring ID is associated with the presence of internalizing and externalizing problems among autistic children and adolescents (Mayes et al, 2022; Yarger & Redcay, 2020) but findings have been inconsistent. While some studies have suggested that co‐occurring ID may exacerbate some types of internalizing and externalizing problems in autistic children (Kurzius‐Spencer et al, 2018; Mayes, Calhoun, Murray, Ahuja, & Smith, 2011; Totsika, Hastings, Emerson, Lancaster, & Berridge, 2011) others have found no significant association between ID and conduct disorders in autistic children (Goldin et al, 2014; Simonoff et al, 2008) or between IQ scores and internalizing problems (Gjevik et al, 2011; Simonoff et al, 2008; Strang et al, 2012; van Steensel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%